Financial market development, global financial crisis and economic growth: evidence from developing nations - Ahmad, R.; Etudaiye-Muhtar, O.F.; Matemilola, B.T.; Bany-Ariffin, A.N. (Springer Verlag (Germany), 2016)
Emerging and frontier markets in Africa have witnessed various economic and financial reforms aimed at integrating the domestic markets into the global financial market to attract investment. Whether these reforms promote high economic growth remains inconclusive. The paper applies the pooled mean group estimation technique to empirically re-investigate the link between financial market development, global financial crisis, and economic growth in selected African economies. The results strongly support our hypotheses that stock market and banking sector development promotes economic growth in the selected countries. Moreover, financial crisis reduce the positive effects of both the stock market and banking sector developments on economic growth. The study suggests that both the banking sector and stock market are important to deliver the long-run economic growth that the African region desired. Moreover, effort should be made to enact policy measures that would ensure development of the stock market which has received inadequate attention.